Case Law of the ECtHR in the Legal System of the Russian Federation and the Challenges Faced by the Judicial Rulemaking - Kuchin, Mihail Victorovich; Gulyaeva, Elena Evgenyevna (Frontiers in Law, 2023)
The article deals with the problem of determining the place and significance of international case law in the legal system of the Russian Federation. On the basis of analysis of international and domestic legal acts and judicial practice existing contradictions are identified and ways to resolve them are offered. Methodology: The research uses general scientific and special cognitive techniques wherein legal analysis and synthesis, systemic, formal-legal, comparative-legal, historical-legal and dialectical methods are applied.